The Influence of Service Innovation, Price, and Destination Image on Tourist Loyalty in Bukit Tinggi Indonesia Tourism - Hayati, Soufiana; Widodo, Slamet (Yayasan Sinergi Kawula Muda, 2024)
This study aims to examine the influence of service innovation, price fairness, and destination image on tourist loyalty in Bukit Tinggi, Padang. The study employed a quantitative method with an associative design and Structural Equation Modeling Partial Least Squares (SEM PLS) analysis. The sample consisted of 120 tourists visiting Bukit Tinggi. Results indicated that service innovation, price fairness perception, and destination image significantly and positively influence tourist loyalty. The practical implications underscore the need for destination managers to enhance service innovation, price transparency, and positive destination image to foster tourist loyalty. The study contributes theoretically by strengthening the understanding of factors influencing tourist behavior in tourist destinations, particularly in the context of Bukit Tinggi.